Risk management: approach and methodology in Carlsberg - Aggerholm, Vibeke P. (Henry Stewart Talks, 2013)
What is Risk Management at Carlsberg, Risk Management framework at Carlsberg, Benefits of effective Risk Management, Risk Management governance structure, Risk Management process (practical guidelines), New and emerging risks (escalation procedure)
Reviewed at 2018/09/27